Covid Impact on Tourism Profit and Cash Holding - Anggita Langgeng Wijaya; Karuniawati Hasanah; Linda Puspita Sari (Profesional Muda Cendekia Publishing, 2022)
The Covid-19 pandemic has significantly impacted various socio-economic aspects of Indonesian society. Tourism activities are a sector directly affected by the harmful effects of Covid-19. The implementation of restrictions on community activities to overcome the Covid-19 pandemic has made tourism business activities experience financial difficulties, leading to business bankruptcy. This study analyzes local tourism companies' profitability and cash holdings in Umbul, Madiun, and East Java before and during the Covid-19 pandemic. This study uses a descriptive qualitative approach. The research data was obtained through observation, interviews, and analysis of the company's financial data. The results of this study indicate a decrease in profitability and a decrease in cash holdings for local tourism companies in Umbul, Madiun during the Covid-19 pandemic. A decrease in profitability and a decrease in cash holdings can be interpreted as an increase in business risk leading to financial difficulties. Local tourism companies Umbul Madiun are advised to focus on the company's cash conversion cycle, more conservative accounting and business policies, and focus on activities that directly impact the number of tourist visits. This strategy is expected to increase the company's profitability, the efficiency of cash holdings management, and efforts to revive the tourism business after the pandemic conditions at the local tourism company Umbul Madiun.